Bioconversion of agro-industrial wastes: Combined compost and vermicompost processes using Eisenia fetida for stabilization of poultry litter - Carolina Elisabet Masin; Maria Emilia Fernandez; Maia Raquel Lescano; Cristina Susana Zalazar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose A combined treatment of composting and vermicomposting of poultry litter (PL), rice hulls (RH) and/or eucalyptus sawdust (ES) was carried out in order to obtain a high-quality organic fertilizer and avoid the environmental problems associated with the use of raw poultry manure and fresh agricultural waste materials. Methods Three composting mixtures were made at volume proportions: 1:3 RH/PL (M1); 1:2 ES/PL (M2) and 0.5:1:2 RH/ES/PL (M3). Composting (120 days) followed by vermicomposting (90 days) using earthworms (Eisenia fetida) were conducted during the autumn-winter season, outdoors and sheltered. Moisture content was kept at 60-70%. Physicochemical (pH, electrical conductivity, lignin, total carbon and nitrogen, organic matter, ammonium and specific cations), total microbial activity (fluorescein diacetate hydrolysis) and microbiological parameters were recorded throughout both processes. Phytotoxicity tests were lastly performed by means of Lactuca sativa, L. seed germination, to compare the quality of the organic fertilizers obtained. Results A sequential compost-vermicompost process enhanced the properties of the final products. Particularly, electrical conductivity was markedly lower in all vermicomposts (1.81-2.28 mS cm-1) and within the values recommended for the growth of sensitive plants; microbial activity reached 187.1-203.8 µg FDA gsoil-1 h-1. Germination Index values in vermicomposts were greater than 60%, indicating the high quality of the products obtained, being the mixture 0.5RH:1ES:2PL, the one which showed better quality and higher maturation degree. Conclusion The system that combines both processes (composting+vermicomposting) was effective to produce a stabilized organic fertilizer from poultry litter with other waste organic materials.